Attitude of the youth of Serbian nationality to the entrepreneurship: The case of Kosovo and Metohia - Stojčetović Bojan; Šarkoćević Živče; Marjanović Danijela (Ekonomski Pogledi, 2015)
The objective of study is to show attitude of the youth in Kosovo towards entrepreneurship. For data collection is used a questionnaire, and the survey included a sample of 200 young people living in the territory of Kosovo and Metohija. Results of the research should demonstrate the reasons of youth for start a business, the amount of funds that are willing to invest, the risk that they are willing to accept, the expected profit and the factors that are critical to the success of businesses in the opinion of the youth. Also, the survey results should show the perceptions of young people about the specifics of business in the territory of Kosovo and Metohija.